VP2 of Chicken Anaemia Virus Interacts with Apoptin for Down-regulation of Apoptosis through De-phosphorylated Threonine 108 on Apoptin. Issue 1 (December 2017) - Lai, Guan-Hua; Lien, Yi-Yang; Lin, Ming-Kuem; Cheng, Jai-Hong; Tzen, Jason; Sun, Fang-Chun; Lee, Meng-Shiunn; Chen, Hsi-Jien; Lee, Meng-Shiou
Abstract Chicken anaemia virus (CAV) is an important contagious agent that causes immunosuppressive disease in chickens. CAV Apoptin is a nucleoplasmic shuffling protein that induces apoptosis in chicken lymphoblastoid cells. In the present study, confocal microscopy revealed co-localisation of expressed CAV non-structural protein VP2 with Apoptin in the nucleus of MDCC-MSB1 cells and the nucleoplasmic compartment of CHO-K1 cells.In vitro pull-down andex vivo biomolecular fluorescent complementation (BiFC) assays further showed that the VP2 protein directly interacts with Apoptin. Transient co-expression of VP2 and Apoptin in MDCC-MSB1 cells significantly decreased the rate of apoptosis compared with that in cells transfected with the Apoptin gene alone. In addition, the phosphorylation status of threonine 108 (Thr108) of Apoptin was found to decrease upon interaction with VP2. Although dephosphorylated Thr108 did not alter the subcellular distribution of Apoptin in the nucleus of MDCC-MSB1 cells, it did suppress apoptosis. These findings provide the first evidence that VP2 directly interacts with Apoptin in the nucleus to down-regulate apoptosis through alterations in the phosphorylation status of the latter. This information will be useful to further elucidate the underlying mechanism of viral replication in the CAV life cycle.